A Bundle of Bundles of Rights – International Treaties Regarding Migration in the Light of the Theory of Property Rights - Schlegel, Stefan (Utrecht Journal of International and European Law, 2018)
A growing body of literature has recently discussed the access of migrants to property rights over assets as a requirement for the protection of their human rights and basic interests. Little attention has been paid, however, to the fact that the right to decide over an individual’s migration to a given place is itself a property right. This paper aims to close this gap by describing international treaties regarding migration as mechanisms to transfer bundles of such property rights. This approach embarks to compare the distributional effects of different treaties regarding migration. It also aims to demonstrate that such treaties often do not limit themselves to transactions of property rights among States, but are capable of transferring property rights from States to individuals. A property rights approach highlights that the exclusion of would-be immigrants from would-be receiving countries means to impose a (negative) external effect on them and their country of origin. A review of different types of treaties demonstrates the tendency in all of these treaties to internalise such external effects. The paper thus predicts that the prevention of migration will get more expensive as the external effects of this activity will have to be internalised to a growing degree.